2004
DOI: 10.1055/s-2004-825652
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Volunteer Work: Contexts for AD Language and Memory Interventions

Abstract: This article describes two novel contexts for language and memory stimulation in individuals with Alzheimer's disease (AD): student-supervised physical exercise and partnered volunteering at community agencies. Information presented is based on 5 years of the authors' experiences at the University of Arizona supervising student-administered interventions with mildly to moderately affected home-dwelling AD patients in the Volunteers in Partnership and Elder Rehab programs. The authors report significant mood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In a recent study, Williams and Tappen [34] observed an antidepressant effect of exercise in severe AD. However, such investigations are still scarce and very little is known about the efficiency of exercise as a protective factor in AD [31,[34][35][36][37][38][39][40] ( table 2 ).…”
Section: Physical Exercise and Alzheimer's Diseasementioning
confidence: 99%
“…In a recent study, Williams and Tappen [34] observed an antidepressant effect of exercise in severe AD. However, such investigations are still scarce and very little is known about the efficiency of exercise as a protective factor in AD [31,[34][35][36][37][38][39][40] ( table 2 ).…”
Section: Physical Exercise and Alzheimer's Diseasementioning
confidence: 99%
“…SLPs should work with the patient and family to modify previous hobbies to fit current functional and cognitive abilities in order to minimize isolation and to ensure that the individual continues to stay mentally engaged. For example, a person who enjoyed volunteering at a community center could continue to do this with the understanding that tasks must be continually modified to meet the person's abilities (Mahendra & Arkin, 2004). …”
Section: Quality Of Life Interventionsmentioning
confidence: 99%
“…Outcomes have been reported in detail elsewhere. [28][29][30][31] Participants showed significant increases over time on all physical fitness indicators, and two-thirds of participants achieved their best aerobic exercise durations after only one or two semesters in the program. 31 A significant decrease in depression symptoms was observed for participants who remained in the program for four or more semesters (i.e., 2 or more years).…”
Section: Introductionmentioning
confidence: 98%
“…[28][29][30][31] Participants showed significant increases over time on all physical fitness indicators, and two-thirds of participants achieved their best aerobic exercise durations after only one or two semesters in the program. 31 A significant decrease in depression symptoms was observed for participants who remained in the program for four or more semesters (i.e., 2 or more years). 31 To assess effects on cognitive performance, the authors compared change scores on selected cognitive measures to annual change data from the CE-RAD registry, 38 a large cohort of persons with AD who were not enrolled in any systematic intervention programs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation